A systematic review and meta-analysis of traditional insect Chinese medicines combined chemotherapy for non-surgical hepatocellular carcinoma therapy - Zhaofeng Shi (Nature Portfolio, 2017)
Abstract On the background of high morbidity and mortality of hepatocellular carcinoma (HCC) and rapid development of traditional Chinese medicine (TCM), we conducted a systematic review and meta-analysis of randomized clinical trials (RCTs) according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement to assess the clinical effectiveness and safety of traditional insect Chinese medicine and related preparation for non-surgical HCC. RCTs were searched based on standardized searching rules in mainstream medical databases from the inception up to May 2016. Ultimately, a total of 57 articles with 4,651 patients enrolled in this meta-analysis. We found that traditional insect Chinese medicine and related preparation combined chemotherapy show significantly effectiveness and safety in objective response rate (P < 0.001), survival time extension [12 months (P < 0.001); 18 months (P < 0.001); 24 months (P < 0.001); 36 months (P < 0.001)], amelioration for life quality [QoL scores improvement (P < 0.001); KPS improvement (P < 0.001); AFP improvement (P < 0.001)] and reduction of therapeutic toxicity [WBC decrease (P = 0.04); gastrointestinal adverse reactions (P < 0.001)]. In conclusion, traditional insect Chinese medicine and related preparations could be recommended as auxiliary therapy combined chemotherapy for HCC therapy.